The power of detention in the management of non-compliance with tuberculosis treatment: A survey of Irish practitioners and analysis of potential legal liability - Duffy, S.T. (Public Health, 2009)
OBJECTIVES: The detention of patients infected with tuberculosis has recently been the subject of significant professional and public interest. In Ireland, the power to detain and isolate probable sources of infectious disease is found in the Health Act 1947. The objective of this study was to describe the use of the power to detain, and to examine relevant legal implications. STUDY DESIGN: Cohort survey. METHODS: Respiratory and infectious disease physicians practising in the public sector were invited to complete a self-administered postal questionnaire. RESULTS: Of the 44 clinicians surveyed, 33 responded, representing a total of 356 years of specialist practice (mean 10.8 years). Although 70% of respondents had made use of threats of formal detention in dealing with non-compliant patients, only one formal detention under statutory powers was identified. Infrastructural and legal concerns with the use of detention were common. There was widespread support for a broadening of the range of additional public health powers, including a power of prolonged detention in the setting of multi-drug-resistant tuberculosis. CONCLUSION: Detention and isolation of non-compliant tuberculosis patients remains in active use. Physicians detaining, or threatening to detain, patients continue to expose themselves to legal liability because of the outdated legal framework underlying those powers.